Inhabitant practices in gardens around houses Case study: Seriana at Batna city - Hamouda , Abida; Nezzar , Sabrina; Aiche , Aicha (Journal of Architecture and environment of child, 2020)
The inhabitant aspires, in the design of his housing, to a quality space including a garden nearby. In this work we will approach the private gardens of some individual houses located in two residential areas in Seriana in the province of Batna in Algeria. Each garden is characterized by a particular typology of form, trees and uses. This study describes how the owner sees the garden through his gardening practice. It turned out that the user is a key player in improving the urban living environment by creating and maintaining its garden.